PERANAN TEKNOLOGI PENDIDIKAN TERHADAP PENINGKATAN KUALITAS SUMBER DAYA MANUSIA - Wartomo . (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2018)
The government programs of Joko Widodo and Yusuf Kalla are contained in NawaCita, among others, to bring the country back to protect the entire nation and to provide a sense ofsecurity to all citizens, as well as improve the quality of life of Indonesians. But the reality is thathuman resources still exist that are involved in corruption, whether human resources from theexecutive, legislative, or judiciary. For that we need to be coaching, training, education anddevelopment for human resources so that truly become a quality human resources. In theimplementation of quality improvement need to use education, and in implementing education usingeducational technology. Educational technology plays a role in improving the quality of humanresources both on physical and health capabilities, intellectual ability, and spiritual (kejuangan). Therole of educational technology can be long-term ie educating students or learners so as to producecandidates for labor as a human resource later on. And also educational technology is used ineducating, training, and developing human resources so as to become a quality human resources,through education that implements educational technology. Educational technology plays a role inimproving the quality of human resources, both in the long term and short term. Suggested that humanresources always develop and improve its performance using education technology. Keywords: Roles, technology, education, and human resources.Â